2001
DOI: 10.1021/bi010288k
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Rac1−RhoGDI Complex Involved in NADPH Oxidase Activation,

Abstract: A heterodimer of prenylated Rac1 and Rho GDP dissociation inhibitor was purified and found to be competent in NADPH oxidase activation. Small angle neutron scattering experiments confirmed a 1:1 stoichiometry. The crystal structure of the Rac1-RhoGDI complex was determined at 2.7 A resolution. In this complex in which Rac1 is bound to GDP, the switch I region of Rac1 is in the GDP conformation whereas the switch II region resembles that of a GTP-bound GTPase. Two types of interaction between RhoGTPases and Rho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
141
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(149 citation statements)
references
References 43 publications
5
141
0
3
Order By: Relevance
“…This difference may be because GTP-Rac binds less well to GDI, or because, in vivo, GTP-Rac interacts with effector proteins that limit its access to GDI. The latter is based on both structural studies showing that effector interaction sites on Rho GTPases overlap with GDI-binding sites (Abdul-Manan et al, 1999;Mott et al, 1999;Hoffman et al, 2000;Scheffzek et al, 2000;Grizot et al, 2001) and direct measurements (Del Pozo et al, 2002). Although dissociation of G12VRac at membrane protrusions is substantially slower, the rate is not negligible (half-time 173 s), consistent with the substantial amount of cytosolic G12VRac complexed with RhoGDI ( Figure 4F and Del Pozo et al, 2002).…”
Section: Discussionmentioning
confidence: 52%
“…This difference may be because GTP-Rac binds less well to GDI, or because, in vivo, GTP-Rac interacts with effector proteins that limit its access to GDI. The latter is based on both structural studies showing that effector interaction sites on Rho GTPases overlap with GDI-binding sites (Abdul-Manan et al, 1999;Mott et al, 1999;Hoffman et al, 2000;Scheffzek et al, 2000;Grizot et al, 2001) and direct measurements (Del Pozo et al, 2002). Although dissociation of G12VRac at membrane protrusions is substantially slower, the rate is not negligible (half-time 173 s), consistent with the substantial amount of cytosolic G12VRac complexed with RhoGDI ( Figure 4F and Del Pozo et al, 2002).…”
Section: Discussionmentioning
confidence: 52%
“…The 19 amino-acid insert sequence present in Rac1b is positioned immediately downstream of switch II, a region known to be involved in effector binding (Bishop and Hall, 2000) as well as interactions with regulatory proteins such as GEFs and GDIs (Ihara et al, 1998;Worthylake et al, 2000;Grizot et al, 2001;Karnoub et al, 2001). Consistent with this possibility, two recent studies found that Rac1b was impaired in RhoGDI and PAK effector, but not GAP, interaction.…”
Section: Discussionmentioning
confidence: 90%
“…Experimental evidence has focused on the Rho family-small GTPase Rac1 as a potential intermediate in the hypoxia signal-transduction pathway. Rac1 regulates assembly of the active NAD(P)H oxidase complex and is recognised as a critical determinant of intracellular redox status [37]. Recent data indicate that Rac1 is required for the induction of HIF-1α protein expression and HIF-1α-dependent gene transcription in response to hypoxia, although Rac1-independent signals are also required for HIF-1α activation under non-hypoxic conditions [11].…”
Section: Discussionmentioning
confidence: 99%